Battery energy storage systems (bess) state of the art. Issue 1 (February 2021) - Jose, Deepa; Meza, Jhonatan; Prashanth, J S
Summary: This article presents a review of the battery energy storage method or BESS for its acronym in English (Battery Energy Storage System), considering that the era of high capacity storage batteries is approaching and why historically the storage of energy did not appear in the planning or operation of electrical systems. However, this solution is currently setting a global trend for having high levels of efficiency and why it is also being driven by the need to modernize the network in order to increase the use of renewable energies.